Performance of a Cold Formed Steel Pedestrian Bridge under Static and Dynamic Loads - Ali Awaludin; Maria Yasinta Menge Making; muhammad Nur Ikhsan; Yohan Adiyuano (Civil Engineering Dimension, 2021)
This paper summarizes new application of CFS in bridge constructions where a seven meters long pedestrian bridge was constructed. The bridge has 1.2m width, 0.8m depth, and is composed of CFS Warren truss and bondek floor systems. Natural frequency of the bridge considering only dead load application was found as 8.54 Hz and decreased to 7.08 Hz when the live load was included. Under static load test, the application of dead load only and both dead and live loads yielded a maximum deflection of 3.53 and 8.1 mm, respectively. Normal walking and running pedestrian loads were carried out created a maximum acceleration equaled to 0.11g. Lastly, sinusoidal waves application facilitated through a three-phase induction motor having self-weight of 24.86 kgf at frequency equal to 8.5 Hz was performed for one hour resulting no decrease of the natural frequency, thus the bridge can be assumed to experience no noticeable stiffness degradation.